2018
DOI: 10.2991/itmr.7.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Commerce on Consumer Decisions

Abstract: Today, comprehending consumer behavior is becoming dynamically challenging with the emergence of social commerce. Business organizations are now striving to convince consumers by exploiting the advantage of social support empowered by online social networks. Importantly, social ties in such online social networks facilitate trust as the most compelling benefit while alleviating the perceived risk, which happened to be the major concerns with electronic commerce over the years. This research study is aimed at u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
(93 reference statements)
1
8
1
Order By: Relevance
“…(3) assessment of performance alternatives; and (4) application of the decision rule. Hettiarachchi et al (2018) found a significant and positive relationship between alternative evaluation and purchase intention. The fact that Instagram Commerce provides information on numerous brands leads users to use it as a tool for evaluating alternatives before making a purchase.…”
Section: 45mentioning
confidence: 88%
“…(3) assessment of performance alternatives; and (4) application of the decision rule. Hettiarachchi et al (2018) found a significant and positive relationship between alternative evaluation and purchase intention. The fact that Instagram Commerce provides information on numerous brands leads users to use it as a tool for evaluating alternatives before making a purchase.…”
Section: 45mentioning
confidence: 88%
“…Lu et al [71] refer social commerce to the use of social media platforms to deliver the various transactions and activities of e-commerce. On the other hand, Hettiarachchi et al [49] define social commerce as an Internet-based social media that facilitates the active participation of people in selling and marketing of services and products through online communities and marketplaces. Another description of social commerce is provided by [67] as a category of e-commerce that utilizes Web 2.0 social media technologies for facilitating online interaction and contributions of online users in acquiring products and services.…”
Section: Social Commercementioning
confidence: 99%
“…, 2020). It allows the consumers to participate in purchasing activities that include comparing, curating, social commerce purchase process and sharing of products and services either the online or offline marketplace or both (Bajwa and Goyal, 2017; Hettiarachchi et al. , 2018; Maia et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social commerce platforms harness the capacities of social media by allowing customers to extend their shopping experience beyond what traditional e-commerce can provide (Cutshall et al, 2020). It allows the consumers to participate in purchasing activities that include comparing, curating, social commerce purchase process and sharing of products and services either the online or offline marketplace or both (Bajwa and Goyal, 2017;Hettiarachchi et al, 2018;Maia et al, 2018;Zhou et al, 2013). Besides, it innovates the static electronic commerce website into an interactive dynamic new sales channel environment (Ngai et al, 2015;Guo and Hu, 2014).…”
Section: Pastry Productsmentioning
confidence: 99%